How resilient were we in 2021? Results of a LinkedIn Survey including biomedical and pharmaceutical professionals using the Benatti Resiliency Model - Songmao Zheng; Karthik Venkatakrishnan; Beth Benatti Kennedy (Wiley, 2022)
Abstract Enhancing resiliency should elevate innovation and efficiency in biomedical research and development (R&D); however, compared with other professions, data on practice of resilience is lacking. Using the Benatti Resiliency Model (5 anchors: Well‐Being, Self‐Awareness, Brand, Connection, and Innovation), we surveyed professionals, including those in biomedical and pharmaceutical R&D. A structured LinkedIn questionnaire (March 16-May 23, 2021), surveyed each model anchor using five categories. One hundred fifty‐eight participants (~6% student/trainee, 18%, 27%, and 49% in 1-5, 5-15 or >15 years post‐terminal degree) took the survey (90 in biomedical and pharmaceutical R&D). Over 50% chose "always"/"often" across questions, except external influence or engagement. The question with one of the lowest "always" scores (~15%) was "I get feedback on my influence and impact in my career" in Brand, highlighting areas for leadership development and coaching. In the anchor of Well‐being, nutrition and stress management also received some lowest "always" scores (~15% for both). Connection and Innovation scores trended slightly higher in biomedical and pharmaceutical R&D. No students/trainees chose "always" in Brand, indicating evolution of brand maturity over time. Self‐ and survey‐assessed resiliency scores were associated (rs = 0.37, p < 0.0001). Our survey yielded actionable insights on Resilience, including "best practices" through an open‐ended question for one thing most useful to boost resilience in the survey and is the first application of the Benatti Model for crowdsourced research.